Bifurcation of Limit Cycles by Perturbing a Piecewise Linear Hamiltonian System - Yanqin Xiong; Maoan Han (Abstract and Applied Analysis)
This paper concerns limit cycle bifurcations by perturbing a piecewise linear Hamiltonian system. We first obtain all phase portraits of the unperturbed system having at least one family of periodic orbits. By using the first-order Melnikov function of the piecewise near-Hamiltonian system, we investigate the maximal number of limit cycles that bifurcate from a global center up to first order of ε.